2023
DOI: 10.1001/jamadermatol.2022.6192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dupilumab in Patients With Erythrodermic Atopic Dermatitis

Abstract: ImportanceErythrodermic atopic dermatitis (AD) is a severe AD subtype defined by extensive skin involvement, leading to complications and sometimes hospitalization.ObjectiveTo assess dupilumab’s efficacy and safety in patients with erythrodermic AD in clinical trials.Design, Setting, and ParticipantsThis post hoc analysis included patients enrolled in 6 multicenter, multinational, randomized, double-blind, placebo-controlled trials. Patients included in this analysis met erythrodermic AD criteria of 90% or gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The major strength of this analysis is that the data are derived from 6 double-blind RCTs with international representation and a total sample size of 209 patients, the largest known evaluated data set of patients with erythrodermic AD . One of the main limitations of this analysis is its retrospective post hoc nature.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…The major strength of this analysis is that the data are derived from 6 double-blind RCTs with international representation and a total sample size of 209 patients, the largest known evaluated data set of patients with erythrodermic AD . One of the main limitations of this analysis is its retrospective post hoc nature.…”
mentioning
confidence: 96%
“…Of the 3075 randomized patients in the study, 209 adolescents and adults met criteria for erythrodermic AD at baseline and 183 completed 16 weeks of treatment with dupilumab . Not surprisingly, patients with erythrodermic AD had worse quality of life at baseline.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors assumed that both drugs were effective in treating these dermatoses [52]. There are fewer reports on the treatment of erythrodermic atopic dermatitis, but some studies have shown the efficacy of dupilumab in treating erythrodermic atopic dermatitis [53,54].…”
Section: Treatmentmentioning
confidence: 99%